2021
DOI: 10.3390/molecules26061734
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Models for Active Substances against Pseudomonas aeruginosa Using Disk-Diffusion Test Data

Abstract: Pseudomonas aeruginosa is a Gram-negative bacillus included among the six “ESKAPE” microbial species with an outstanding ability to “escape” currently used antibiotics and developing new antibiotics against it is of the highest priority. Whereas minimum inhibitory concentration (MIC) values against Pseudomonas aeruginosa have been used previously for QSAR model development, disk diffusion results (inhibition zones) have not been apparently used for this purpose in the literature and we decided to explore their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
0
4
0
1
Order By: Relevance
“…In developing Quantitative Structure-Activity Relationship (QSAR) models, selecting molecular descriptors is of paramount importance [5]. These models’ effectiveness hinges on using unique and carefully chosen descriptors [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing Quantitative Structure-Activity Relationship (QSAR) models, selecting molecular descriptors is of paramount importance [5]. These models’ effectiveness hinges on using unique and carefully chosen descriptors [5].…”
Section: Methodsmentioning
confidence: 99%
“…In developing Quantitative Structure-Activity Relationship (QSAR) models, selecting molecular descriptors is of paramount importance [5]. These models’ effectiveness hinges on using unique and carefully chosen descriptors [5]. An optimal set of descriptors should capture the essential molecular characteristics relevant to the study while avoiding redundancy.…”
Section: Methodsmentioning
confidence: 99%
“…A study developed multiple QSAR methods using several ML algorithms, including SVM, to predict the activity of active substances against Pseudomonas aeruginosa. The study found that SVM could better predict the compounds' activity accurately compared to other models [80]. Another study examined SVM's effectiveness and prognostication power in HEPT derivative QSAR modeling.…”
Section: Support Vector Machinementioning
confidence: 99%
“…The study found that SVM could better predict the compounds' activity among other models accurately. 77 Another study investigated SVM's performance and predictive capability in QSAR modeling of HEPT derivatives. This study compared SVM with other methods, such as artificial neural networks, and found that SVM achieved good predictive performance.…”
Section: Support Vector Machinementioning
confidence: 99%